Pengaruh Konsentrasi Sukrosa terhadap Karakteristik Wine Jeruk Siam Kintamani (Citrus nobilis L.) - Febian, Gilbert; Wisaniyasa, Ni Wayan; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 3 (2024): Jurnal ITEPA, 2024)
Kintamani Siamese oranges are one of Bali’s local fruits. There is a problem during harvest season, namely the price of oranges falls due to oversupply. To solve the problem, it is necessary to utilize kintamani Siamese oranges into a product to extend their shelf life and increase their economic value. One way to utilize it is to make wine . However, Siamese kintamani orange lacks natural sugar in it. Therefore, an external source of sugar is needed and sucrose is a sugar source that is commonly used in wine making. This research aims to determine the effect of sucrose concentration on the characteristics of Kintamani Siamese orange wine and the right concentration of sucrose to produce kintamani Siamese orange wine with the best characteristics. The research conducted with completely randomized design with factor of sucrose concentration that consisting of five concentration levels namely: 10, 15, 20, 25, 30% (w/v). The treatment repeated three times resulting 15 experimental units. The data were analysed by Analysis of Variance (ANOVA) and the treatment that showed effect was observed by Duncan’s Multiple Range Test (DMRT). The results showed that sucrose concentration had effect on ethanol content, total acid, total dissolved solids, color, taste, overall acceptability, and obtained negative results in the methanol content test. Kintamani Siamese orange wine with sucrose concentration of 15% produced the best kintamani Siamese orange wine with an ethanol content of 10,54%, methanol content was not detected, total dissolved solids of 8,47°brix and total acid of 1,10% and obtained a color that liked by the panel, aroma somewhat liked, taste is neutral, and overall acceptability is somewhat liked. Keywords: Kintamani Siamese orange, wine, sucrose, characteristics